Analysis of Service Implementation from the Perspective of Excellent Service to Enhance Member Satisfaction : A Case Study of the Soybean Trade Unit at KOPTI Bandung - Nanik Risnawati; Dhyta Marliani (J-Coop : Journal of Co-operative, 2025)
This study analyzes the service implementation of the soybean trade unit at KOPTI in Bandung City, which faces two main challenges: the inability to meet the annual distribution target of 4,200,000 kg and a high level of member passivity, with more than 67% of members being inactive during the 2019–2023 period. Member dissatisfaction with cooperative services is suspected to be the primary cause of these issues, as the service delivery has yet to reach an optimal level. The research aims to examine the implementation of KOPTI's services, evaluate member responses and expectations, measure member satisfaction levels, and identify necessary measures to improve service quality. The study employs a descriptive case study method with an in-depth approach through interviews, questionnaires, and direct observations. The analysis is conducted using a Cartesian diagram to identify priority areas for improvement. The findings reveal that, overall, KOPTI's services are considered adequate by both active and passive members. However, several service aspects, including soybean pricing, quality consistency, responsiveness to member requests, and soybean availability, fall into quadrant I of the Cartesian diagram, indicating the need for immediate improvement. To enhance member satisfaction more effectively, KOPTI must address these priority areas and improve the overall implementation of its services. These improvements are expected not only to boost member satisfaction but also to encourage active participation, ultimately contributing to the cooperative's achievement of its annual targets.